Synthesis of macrocyclic and linear oligomers of methyl a-D-mannopyranoside - Maślińska-Solich, J.; Kukowka, S. (Polimery, 2022)
The polycondensation of methyl a-D-mannopyranoside (I) with 1,x-bis(2-formylphenoxy)alkanes (II) using various acid catalysts leads to the formation of macrocyclic compounds [1+1] and [2+2] and linear copolymer. NMR and ESI-MS studies demonstrated the evidence of structure of macrocyclic compounds. The structure of dialdehyde, the nature of the catalyst, and in particular, the molar ratio of catalyst to dialdehyde, show a very pronounced effects on yield of the resulting macrocycles.